The Boondock Saints - Duffy, Troy.; Connolly, Billy, 1942-; Brian Mahoney; David Della Rocco; David Ferry; Norman Reedus; Sean Patrick Flanery; Willem Dafoe (Canada, USA B.D.S. Productions Inc, 1999)
Two Irish brothers accidentally killed mafia thugs. They turned themselves in and were released as heroes. They then see it as a calling by God and started knocking off mafia gang members one by one. Willem Dafoe plays the detective trying to figure out the killings, but the closer he was to catching the Irish brothers, the more he thinks the brothers are doing the right thing.
Fraternal twins set out to rid Boston of the evil men operating there while being tracked down by an FBI agent.
Troy Duffy
Languages : English, Turkish Subtitles : English, Turkish
Keywords: Drama; Thriller; Crime